Linguodidactic Features of the Development of Oral Speech Competence of Students in the Field of Physical Culture Education (In the Example of Sports Terms) - Abdisalimovich, Kenjabaev Jahongir (INTERNATIONAL CONFERENCE ON MULTIDISCIPLINARY RESEARCH AND INNOVATIVE TECHNOLOGIES, 2021)
The article deals with the method of teaching students by techniques concerned with vocabulary. Pragmatic aspect of foreign language teaching is related to the formation of students’ knowledge, skills and abilities, their knowledge allows them to get acquainted with the ethnic and cultural values of the country studied and practical use of a foreign language in intercultural understanding. The combination of such knowledge, skills and abilities is the communicative competence of the learners. The concept of communication is the result of ongoing efforts between a person’s scientific and interpersonal communication skills.